2019
DOI: 10.1590/1518-8345.3170.3241
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and manual registration of Manchester System: reliability, accuracy, and time evaluation

Abstract: Objective:to evaluate the degree of reliability, accuracy and timing to perform the Manchester Triage System in electronic and manual records.Method:exploratory-descriptive research. Case series corresponded to a total of 20 validated simulated clinical cases applied to a sample of 10 nurses. For data collection each participant received 4 clinical cases in 2 different phases of the study, using manual and electronic registration. The variables related to the triage were: incomplete data filling, discriminator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
10
0
4
Order By: Relevance
“…For the evaluators, this characteristic was over 90%, which reflects users' confidence in the system. We stress that the reliability of computerized systems has shown higher rates when compared to manual systems (9,14) .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For the evaluators, this characteristic was over 90%, which reflects users' confidence in the system. We stress that the reliability of computerized systems has shown higher rates when compared to manual systems (9,14) .…”
Section: Discussionmentioning
confidence: 88%
“…In the information age, alternatives to health registering have been proposed in order to find strategies to store and qualify data registration, to build safer and more quality health care ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Using tools such as the multiparameter monitor to quickly identify the patient's status and computerize the RC protocol can facilitate data collection, reduce RC time, and improve the accuracy of recording all service times. A recent study found that recording in electronic medical records had higher reliability and accuracy for the variable "vital signs", and the time spent with RC was significantly less when compared to the use of manual records (16) .…”
Section: Discussionmentioning
confidence: 99%
“…The presented works reaffirm the importance of the MTS in the risk classification while pointing to some flaws during the process. The works from Cicolo and Peres (2019) and Funchal and Adanatti (2016) were used as a standard for the metrics comparison in this work. Cicolo and Peres (2019) evaluated the accuracy and time taken for the MTS risk classification in manual and electronic devices.…”
Section: Related Workmentioning
confidence: 99%